Additional evidence for early modern human morphological diversity in Southeast Asia at Tam Pa Ling, Laos. (1st February 2018) - Shackelford, Laura; Demeter, Fabrice; Westaway, Kira; Duringer, Philippe; Ponche, Jean-Luc; Sayavongkhamdy, Thongsa; Zhao, Jian-Xin; Barnes, Lani; Boyon, Marc; Sichanthongtip, Phonephanh; Sénégas, Frank; Patole-Edoumba, Elise; et al.
Abstract: Despite its geographic primacy as the intersection of dispersal paths to Australasia, mainland Southeast Asia has played little role in scenarios of early human migrations. Tam Pa Ling (TPL), a cave site in northern Laos, is the source of early modern human fossils – a partial cranium (TPL1) and a complete mandible (TPL2) – that represent the earliest anatomically modern humans in continental Southeast Asia and introduce new migration routes into the region during Marine Isotope Stage 3. In the current analysis, a new partial mandible from the site, TPL 3, is introduced, described, and evaluated using geometric morphometrics in the context of Pleistocene archaic, early modern and Holocene humans. In addition, the sedimentary context of TPL3 is described and refined through further quartz single-grain optically stimulated luminescence (SG-OSL) measurements and additional feldspar post-infrared infra-red stimulated luminescence (pIR-IRSL) techniques. The TPL3 mandible has discrete traits similar to eastern Asian early modern humans, including a well-developed chin and a lack of lateral corporal robusticity. It does, however, retain a relatively broad anterior mandibular arch that is more commonly associated with archaic populations. In this way, it is similar to the TPL2 mandible as well as other similarly-aged fossils from the region that show a mixture of archaic and derived traits. The combined quartz SG-OSL and feldspar pIR-IRSL techniques provide an age range of 70 ± 8–48 ± 5 ka for the depositional age of the layer containing the TPL3 mandible. This upper age estimate is ∼20 ka older than the depositional ages for the TPL1 and 2 fossils, extending the upper limit for the currently excavated sedimentary and associated fossil evidence.